Dynamics of Organizational Behavior Research From 1997–2024: A Bibliometric Study - Anggriani Alamsyah (Universitas Negeri Semarang, 2025)
This article aims to fill the gap on management bibliometrics especially on organizational behavior. The analysis was conducted through data collection by keyword “organizational behavior” in Scopus-indexed journals. There are 150 documents from 96 sources, from 1997 to 2024, collected on October 29, 2024. The accumulated documents are then purified by open refine tools (version 3.8.2) for data refinement. The bibliometric analysis utilized Vosviewer (version 1.6.20), and Rstudio (bibliometric). The result of the bibliometric analysis exposed there are 10 most relevant authors for this research domain with 2 articles for each of them. The top 3 most productive countries are gained by USA, the United Kingdom, and Germany. USA has gained 7 multi-country publications and collected 802 citations. The possible future research for “organizational behavior” could be broadened with themes like: conflict, artificial intelligence, innovation, and work engagement. The originality of this article is exposing bibliometrics of organizational behavior that focuses on the author’s and country’s analysis, as well as the possible future research.